A negative computed tomography may be sufficient to safely discharge patients with abdominal seatbelt sign from the emergency department: A case series analysis. Issue 6 (June 2018) - Barmparas, Galinos; Patel, Deven C.; Linaval, Nikhil T.; Dhillon, Navpreet K.; Patel, Kavita A.; Margulies, Daniel R.; Ley, Eric J.
Abstract : BACKGROUND: The presence of an abdominal seatbelt sign (ASBS) following a motor vehicle collision (MVC) is associated with a high risk for occult intra-abdominal injury, prompting imaging studies and a prolonged period of clinical observation. The aim of this study was to determine how a negative computed tomography (CT) of the abdomen/pelvis (A/P) can serve in the safe disposition of these patients. Our hypothesis was that in the setting of a negative CT, the presence of occult intra-abdominal injuries requiring a delayed intervention is extremely unlikely. METHODS: The medical charts of patients admitted from January 2014 to December 2016 to a Level I trauma center following an MVC were reviewed for a documentation of an ASBS. Patients who did not have a CT A/P upon admission were excluded. The CT A/P of the remaining patients were then classified as negative if there were no findings of acute vascular, visceral or bony injury or positive if any of these findings was present. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of CT A/P for the presence of an intra-abdominal injury were calculated. RESULTS: Over the 3-year study period, 1, 108 patients were admitted after an MVC. Of those, 196 (17.7%) had an ASBS upon presentation and 183 (93.4%) of 196 underwent a CT A/P. A total of 114 (62.3%) of 183 had a negative CT A/P. These patients remained hospitalized for a median of 2 (1–35) days with none (0.0%) requiring a delayed laparotomy. The sensitivity of CT A/P in identifying patients requiring an exploratory laparotomy was 100.0%, specificity was 67.9%, NPV was 100.0%, and PPV was 21.7%. The negative likelihood ratio was 0.00. CONCLUSION: For patients with an ASBS following an MVC, a negative CT A/P may be sufficient for safe discharge from the emergency department without any need for additional clinical observation. LEVEL OF EVIDENCE: Therapuetic, level IV.